« Cancer Alley » ou la décompression du paysage pétrochimique. La collaboration de Richard Misrach et de Kate Orff - Matthieu Duperrex (Les Cahiers de la Recherche Architecturale, Urbaine et Paysagère)
This paper addresses the collaboration between photographer Richard Misrach and landscape architect Kate Orff, which gave way to various creative exhibitions as well as the book, Petrochemical America (2012). The originality of this work can be found in the mobilization of landscape design tools to produce, from the seminal “scene” of photography, a kind of reverse engineering of the industrial landscape factory. In turn, the photographic representation effects – its “punctum” – is amplified through a singular genealogy of the altered landscape.